Réponses

Meilleure réponse !
2014-05-15T19:54:51+02:00
A=6t²-3t+2-5t²-3t-5    
en regroupant par "famille"
A= 6t² - 5t² -3t -3t +2-5
A= t² -6t -3

 B=7a-4b+a+4b 
en regroupant par "famille"
B = 7a+a - 4b+4b
B = 8a 

C=5-(-6x+3)
il faut enlever la parenthèse sans oublier de changer le signe à l'intérieur
C = 5 + 6x - 3
en regroupant par "famille"
C = 5-3 + 6x
C = 2 + 6x 


2014-05-15T19:59:00+02:00
6 x t + 6 x t - 3 x t + 2 - 5 x t + ( - 5 ) x t - 3 x t - 5
6t + 6t - 3t + 2 - 5t + (-5t ) - 3t -5
- 4t -3


c'est pour le A